2011
DOI: 10.1167/11.1.23
|View full text |Cite
|
Sign up to set email alerts
|

Contrast summation across eyes and space is revealed along the entire dipper function by a "Swiss cheese" stimulus

Abstract: Previous contrast discrimination experiments have shown that luminance contrast is summed across ocular (T. S. Meese, M. A. Georgeson, & D. H. Baker, 2006) and spatial (T. S. Meese & R. J. Summers, 2007) dimensions at threshold and above. However, is this process sufficiently general to operate across the conjunction of eyes and space? Here we used a "Swiss cheese" stimulus where the blurred "holes" in sine-wave carriers were of equal area to the blurred target ("cheese") regions. The locations of the target r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(49 citation statements)
references
References 136 publications
1
48
0
Order By: Relevance
“…In summation experiments with these stimuli, performance dropped to the expected factor of ¾2 (3 dB), supporting the model (Meese, 2010). Meese and Baker (2011) proposed that the process of area summation of contrast is involved in deriving a general-purpose size code for textures and patterns. They suggested that this task is achieved with the help of a contrast normalization network (Meese & Baker, 2011;Meese & Summers, 2007) that protects the suprathreshold image-contrast code (Albrecht & Geisler, 1991;Heeger, 1992).…”
Section: Introductionsupporting
confidence: 59%
See 3 more Smart Citations
“…In summation experiments with these stimuli, performance dropped to the expected factor of ¾2 (3 dB), supporting the model (Meese, 2010). Meese and Baker (2011) proposed that the process of area summation of contrast is involved in deriving a general-purpose size code for textures and patterns. They suggested that this task is achieved with the help of a contrast normalization network (Meese & Baker, 2011;Meese & Summers, 2007) that protects the suprathreshold image-contrast code (Albrecht & Geisler, 1991;Heeger, 1992).…”
Section: Introductionsupporting
confidence: 59%
“…A more successful model is one in which contrast integration (linear spatial summation of contrast) follows a nonlinear (square-law) contrast transducer (Foley, Varadharajan, Koh, & Farias, 2007;Meese & Summers, 2007, 2009) and additive noise (Meese, 2010). The cascade of the two quadratic effects produced by square-law transduction (Legge, 1984) and summation of signal and noise (Campbell & Green, 1965;Tyler & Chen, 2000) means that sensitivity improves with the fourth root of area, similar to the conventional probability summation model and several empirical reports (see Meese & Baker, 2011 for a review). However, the behavior of model and humans is very different when contrast area is manipulated in more interesting ways, as we now describe.…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…This lack of consensus probably springs, in part, from the smallness of these effects -just a few dB -coupled with the considerable difficulty of getting reliable, unbiassed threshold estimates to the required accuracy. Over the last 30 years, computer-controlled, forced-choice psychophysical methods with better display technology, and much greater numbers of trials, have improved the reliability of threshold estimation, and with these methods estimates of the binocular advantage tend to cluster around 4-5dB (Legge, 1984;Maehara & Goryo, 2005;Meese & Baker, 2011;Meese et al, 2006;Meese & Summers, 2009;Simmons & Kingdom, 1998;Simmons, 2005) -as if forming a compromise between the theoretically salient values of 3 and 6 dB (which represent an ideal observer with independent noise in the two eyes versus linear summation with fixed noise). In a retrospective analysis, however, we found that the variation between studies may not be random.…”
Section: Relation To Binocular Summation Of Luminance Contrastmentioning
confidence: 99%